Neural correlates of moderate hearing loss: time course of response changes in the primary auditory cortex of awake guinea-pigs - Huetz, Chloé; Guedin, Maud; Edeline, Jean-Marc (Frontiers in Systems Neuroscience, 2014)
Over the last decade, the consequences of acoustic trauma on the functional properties of auditory cortex neurons have received growing attention. Changes in spontaneous and evoked activity, shifts of characteristic frequency (CF), and map reorganizations have extensively been described in anesthetized animals (e.g., Norena and Eggermont, 2003, 2005). Here, we examined how the functional properties of cortical cells are modified after partial hearing loss in awake guinea pigs. Single unit activity was chronically recorded in awake, restrained, guinea pigs from three days before up to 15 days after an acoustic trauma induced by a 5kHz 110dB tone delivered for 1h. Auditory brainstem responses (ABRs) audiograms indicated that these parameters produced a mean ABR threshold shift of 20dB SPL at, and one octave above, the trauma frequency. When tested with pure tones, cortical cells showed on average a 25dB increase in threshold at CF the day following the trauma. Over days, this increase progressively stabilized at only 10dB above control value indicating a progressive recovery of cortical thresholds, probably reflecting a progressive shift from temporary threshold shift (TTS) to permanent threshold shift (PTS). There was an increase in response latency and in response variability the day following the trauma but these parameters returned to control values within three days. When tested with conspecific vocalizations, cortical neurons also displayed an increase in response latency and in response duration the day after the acoustic trauma, but there was no effect on the average firing rate elicited by the vocalization. These findings suggest that, in cases of moderate hearing loss, the temporal precision of neuronal responses to natural stimuli is impaired despite the fact the firing rate showed little or no changes.